2020
DOI: 10.1148/ryct.2020200441
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Reproducibility of AI-assisted Analysis of Lung Involvement in COVID-19 at Low-Dose Submillisievert Chest CT: Sample Size Implications for Clinical Trials

Abstract: To compare the prognostic value and reproducibility of visual versus AI-assisted analysis of lung involvement on submillisievert low-dose chest CT in COVID-19 patients. Materials and Methods: This was a HIPAA-compliant, institutional review board-approved retrospective study. From March 15 to June 1, 2020, 250 RT-PCR confirmed COVID-19 patients were studied with low-dose chest CT at admission. Visual and AI-assisted analysis of lung involvement was performed by using a semi-quantitative CT score and a quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The algorithm uses CT data to automatically identify and 3D-segment both the lung parenchyma and abnormal areas of ground-glass opacities and consolidation. The software outputs a percentage of total lung involvement (by both GGO and consolidation) [23] . Follow-up chest CTA was systematically completed by a volumetric, non-contrast, single-energy acquisition at expiration to detect air trapping, i.e., a potential confounder for perfusion defect interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm uses CT data to automatically identify and 3D-segment both the lung parenchyma and abnormal areas of ground-glass opacities and consolidation. The software outputs a percentage of total lung involvement (by both GGO and consolidation) [23] . Follow-up chest CTA was systematically completed by a volumetric, non-contrast, single-energy acquisition at expiration to detect air trapping, i.e., a potential confounder for perfusion defect interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with Lassau et al [ 22 ], we found an association of clinical severity with increased neutrophils count and neutrophils-lymphocytes ratio. Few studies have combined clinical and biological data with chest CT for prognostication in COVID-19 pneumonia [ 14 , 21 , 22 , 23 ]. Like previous investigators, we demonstrate here that a model integrating AI-based CT scan information and clinical and biological parameters improves the prognosis performance of the score.…”
Section: Discussionmentioning
confidence: 99%
“…Despite two studies showing that lung disease extent in COVID-19 pneumonia assessed by visual scoring correlates with clinical disease severity [ 19 , 20 ], visual estimation of disease extent even done by experimented radiologists may be a source of variability. Artificial Intelligence (AI) software developed to help radiologists in the quantification of lung involvement in COVID-19 may overcome this limitation [ 21 ]. Some investigators developed their own AI system for accurate quantitative measurements and prognosis of COVID-19 pneumonia using CT [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors have recently proposed quantitative methods using open-source platforms to evaluate CT-SS and found that compared with the semi-quantitative visual score, the quantitative CT parameters have superior accuracy ( Figure 12 ) [ 152 , 159 ]. Deep learning algorithms are also promising in the evaluation and quantification of COVID-19 pneumonia [ 160 , 161 ].…”
Section: Chest Ctmentioning
confidence: 99%